Surgical Outcomes after Pulmonary Resection for Non–Small Cell Lung Cancer with Localized Pleural Seeding First Detected during Surgery - Yun, Jae Kwang; Kim, Mi-Ae; Choi, Chang Min; Choi, Se Hoon; Kim, Yong-Hee; Kim, Dong Kwan; Park, Seung-Il; Kim, Hyeong Ryul (The Thoracic and Cardiovascular Surgeon, 2018)
Objectives Curative resection is not indicated for non–small cell lung cancer (NSCLC) with pleural seeding, which is classified as stage IV (M1a) disease. However, some patients with a presumably resectable main tumor are diagnosed with localized pleural seeding during surgery.Methods A retrospective analysis was performed of 3,975 patients who underwent surgery for NSCLC from 2000 to 2011. Among these cases, 78 (2.0%) patients had unexpected pleural seeding detected during surgery. Exploration with pleural biopsy was performed in 42 of these patients (exploration-only group) and pulmonary resection, including for the main tumor, was performed in 36 cases (resection group; sublobar resection in 12, lobectomy in 21, and pneumonectomy in 3 patients). Survival and cancer progression rates were estimated using the Kaplan–Meier method. Cox proportional hazard regression was used to evaluate prognostic factors associated with survival.Results Adenocarcinoma was the predominant histological type in both the exploration and resection groups (88.1 and 86.1%, respectively). Epidermal growth factor receptor expression was detected in 22 (52.4%) patients of the exploration group and 21 (58.3%) patients of the resection group. Baseline characteristics including age, sex, comorbidity, pulmonary function, and clinical T/N status were not significantly different between the two groups. There were no postoperative deaths in either group but postoperative complications occurred in two (4.8%) patients of the exploration group and three (8.3%) patients of the resection group. The overall 3- and 5-year survival rates in the exploration group were 41.1 and 15.2%, respectively, with a median survival time (MST) of 33 months, whereas they were 66.7 and 42.7%, respectively, in the resection group, with a 52-month MST (p = 0.012). Local and regional progression–free rates were significantly different (p < 0.001 and p = 0.029, respectively) between groups, whereas no difference was seen in the distant metastasis rates (p = 0.957). In multivariate survival analysis, surgical resection was the only significant prognostic factor (p = 0.01).Conclusions Pulmonary resection including the main tumor, regardless of resection extent, may increase long-term survival for NSCLC patients with localized pleural seeding first detected during surgery, without a significant increase in hospital mortality or morbidity.
Keywords: lung cancer; metastasis; surgery